2016
DOI: 10.1108/jat-09-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality and robots for autism: moving beyond the screen

Abstract: Purpose -This short paper reports on the fourth seminar in a 7-seminar series entitled, "Innovative Technologies for Autism: Critical Reflections on Digital Bubbles", funded by the UK Economic and Social Research Council (ESRC). The aim of this particular seminar was to consider in more depth the technologies being developed and used in the autism field, and to critically reflect on their relative benefits and potential pitfalls. Design/methodology/approach -Presentations from key researchers and practitioners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Signal Preprocessing Algorithm. rough the communication packet capture tool to capture the data sent by the VR surgery scene, through analysis, it is found that the data packets sent by the VR surgery scene form a first-order step system in each cycle [16]. According to the relevant principles of automatic cybernetics, the mathematical model of the first-order system can exactly represent it correctly [17].…”
Section: Virtual Reality-related Algorithms Based On Intracranialmentioning
confidence: 99%
“…Signal Preprocessing Algorithm. rough the communication packet capture tool to capture the data sent by the VR surgery scene, through analysis, it is found that the data packets sent by the VR surgery scene form a first-order step system in each cycle [16]. According to the relevant principles of automatic cybernetics, the mathematical model of the first-order system can exactly represent it correctly [17].…”
Section: Virtual Reality-related Algorithms Based On Intracranialmentioning
confidence: 99%
“…Many studies have employed humanoid robots for treatment plans for children with ASD [66][67][68][69][70][71][72][73][74][75][76][77][78][79]. However, some research has used non-humanoid robots [11,[80][81][82][83][84].…”
Section: Social Robotsmentioning
confidence: 99%
“…Previous research results show that children with ASD are more responsive to technology than to usual human interaction (e.g. Good et al , 2016; Parsons and Mitchell, 2002; Scassellati et al , 2012). People with ASD are more attuned to the mechanics of mouth movement rather than mouth-eyes feedback processing, according to two literature reviews (Falck-Ytter and von Hofsten, 2011; Guillon et al , 2014), where results confirm this theory for teenagers and adults but are mixed for younger children; and according to a more recent piece of research that shows that children with autism focus on mouth movements during emotional conversations (Hutchins and Brien, 2016).…”
Section: Virtual Play and Empathy In Atypical Developmentmentioning
confidence: 97%